The Real Effects of Implicit Government Guarantee: Evidence from Chinese State-Owned Enterprise Defaults - Jin, Shuang; Wang, Wei; Zhang, Zilong (Management Science, 2023)
We study the effects of implicit government guarantee (IGG) on Chinese state-owned enterprises (SOEs). We find that SOEs reduce their investments by 2.4% of book assets, on average, relative to matched non-SOEs after the first SOE default in China’s onshore bond markets in 2015. The investment reduction concentrates among SOEs that are financially constrained, yet SOEs financed by large state banks are hardly affected. Bondholders require more stringent default protection in newly issued SOE bonds. We also find that the investment reduction is more pronounced for SOEs with severe agency problems and that SOEs experienced more positive market reactions to acquisition announcements after 2015. Our results suggest that the reduction in IGG has confounding effects on Chinese firms. Although the weakening of IGG may help mitigate overinvestment, it exacerbates financial constraints of those with limited access to alternative sources of financing. This paper was accepted by Lucas Schmid, finance. Funding: Z. Zhang acknowledges the funding support by Research Grants Council of Hong Kong [Project 11503318]. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.4483 .